"Pilot" spectator events in British horseracing during COVID‐19: post‐event SMS COVID‐19 reporting. (13th November 2021) - Davies, Madeleine A.M.; Spincer, Mark; Klein, Andre; Walters, Sarah; Wright, Peter; Hurley, Adam; Stokes, Keith; Hill, Jerry
Abstract: This study aimed to assess (i) COVID‐19 transmission prior to and following spectator events and (ii) methodological approaches to capturing event‐related transmission during the spectator return. Local authority population transmission rates were used to identify higher transmission areas, which were excluded from participant attendance following registration. Using observational online and SMS questionnaires, self‐reported COVID‐19 diagnoses (positive tests) and racing‐related NHS Test and Trace contacts within 14 days of spectating were reported for two British Horseracing events and three Point to Point (PTP) grassroots races. There were 1, 477 registrations for the British Horseracing events, and 1, 678 registrations for PTP races. Responses were received from 464 attendees of British Horseracing events (31.4% response rate). Two attendees reported a COVID‐19 diagnosis, and no attendees reported NHS Test and Trace contact. From PTP races, 862 attendees (51.3%) consented to receive the SMS survey, and responses were received from 495 attendees (57.4% response rate). Five attendees reported positive COVID‐19 diagnoses, and two attendees reported being contacted by NHS Test and Trace, of which one was following a non‐racing potential COVID‐19 exposure. There was limited evidence of COVID‐19 transmission at outdoor elite and grassroots level horseracing events during autumn 2020. A higher response rate was received with SMS surveys; however, there was a reluctancy to "opt in" to SMS methodology. This study describes different methodological approaches to monitoring COVID‐19 transmission risk at events, which may have relevance for other sporting and event contexts during the current pandemic, and sustained attendances during periods with circulating transmissible diseases.